Модель асинхронного двигуна із врахуванням втрат у залізі при орієнтуванні координат за потокозчепленням статора - Приймак, Богдан Іванович; Благодір, Віталій Олегович (НТУ "ХПІ", 2010)
A mathematical model of induction motor in stator flux vector oriented frame that account for magnetic iron core power losses is derived.
An induction motor model in stator flux oriented frame that account for iron losses
Keywords: електропривід; модель математична; момент електромагнітний